2021
DOI: 10.1093/ije/dyab189
|View full text |Cite
|
Sign up to set email alerts
|

Attributable risks of hospitalizations for urologic diseases due to heat exposure in Queensland, Australia, 1995–2016

Abstract: Background Heat exposure is a risk factor for urologic diseases. However, there are limited existing studies that have examined the relationship between high temperatures and urologic disease. The aim of this study was to examine the associations between heat exposure and hospitalizations for urologic diseases in Queensland, Australia, during the hot seasons of 1995–2016 and to quantify the attributable risks. Methods We obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
3
12
1
Order By: Relevance
“…Two authors were contacted for additional data not published in the original article. One paper could not share additional data due to Queensland Health not permitting data sharing and hence was excluded 26 . Another paper did not have data for each age category according to rurality and was excluded 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Two authors were contacted for additional data not published in the original article. One paper could not share additional data due to Queensland Health not permitting data sharing and hence was excluded 26 . Another paper did not have data for each age category according to rurality and was excluded 12 .…”
Section: Resultsmentioning
confidence: 99%
“…40 Our subgroup analysis results have some consistencies and inconsistencies with previous studies as well-for example, our findings that men and younger populations are at a higher risk of genitourinary conditions were not quite the same as a previous study in Queensland, Australia that concluded that men and elderly are more vulnerable to heat effects causing genitourinary diseases. 41 While the reason behind this difference remains unclear, it may suggest that the elderly population in Japan has better protection against heat, whether it be through preventative healthcare measures, genetics, or living environments; alternatively, this difference may indicate that the younger population in Japan has a different mobility pattern compared with that in Australia that puts them at an increased risk of exposure. Furthermore, our results differ from another study in South Korea that found that cold spells are associated with hospital admission and mortality due to AKI, especially in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variations in hospital admissions were proven for cardiovascular, genitourinary, or respiratory diseases [ 29 31 ]. In the present study, the highest number of diabetes-related hospitalizations (in both types of diabetes) was observed in January and the lowest in December.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients hospitalized due to type 2 diabetes, the highest in-hospital mortality rate was observed in January and February. We can hypothesize that the weather, air pollution, and limited psychical activity level during winter can increase the risk of in-hospital mortality among patients with type 2 diabetes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%